Teachers, fixed-term contracts and school leadership: Toeing the line and jumping through hoops - Stacey, Meghan; Fitzgerald, Scott; Wilson, Rachel; McGrath-Champ, Susan; Gavin, Mihajla (2021)
Fixed-term contracts are a relatively recent, yet growing category of employment for teachers in the public school system in New South Wales (NSW), Australia. In this article, we draw on quantitative and qualitative data from a large state-wide survey (N = 18,234) of members of the public-school teacher union, the NSW Teachers’ Federation, in order to explore the workload reports of teachers in temporary employment. We find that overall, these teachers report similar levels of workload to staff employed on a permanent basis. Experiences of work are, however, qualitatively different, with many in the temporary category feeling they must work harder than permanent teachers in order to ‘prove themselves’ to school executive. We argue that such experiences of precariousness may have particular ‘scarring’ effects for teachers in temporary employment, including gendered patterns of career progression, and discuss implications for leadership and policy.